2018
DOI: 10.4103/jrms.jrms_979_17
|View full text |Cite
|
Sign up to set email alerts
|

Varicella infection in the Middle East: Prevalence, complications, and vaccination

Abstract: Varicella (chickenpox) is the primary infection of varicella-zoster virus (VZV), it is a mild self-limiting infection, but it is also highly contagious and can cause severe complications among high-risk group of individuals. It is usually a childhood infection providing lifelong immunity, but adults without varicella history are also susceptible to infection. High-risk group of individuals is more likely to develop serious complications. Varicella vaccine was introduced to protect this group of individuals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…The impact data on its effect are available from Saudi Arabia, which introduced universal VV in 2008 with a two dose schedule, and a study using health insurance data found an overall 60% reduction in the proportion of disease in children aged between 1-4 years after introduction. 31,75 Herd immunity and shift to older age groups An indirect effect of VV in non-vaccinated age groups has been described in many studies. As herd immunity is more pronounced in age groups closer to the vaccinated group, there are concerns about a shift of the disease to older age groups, which have a higher rate of complications.It is more likely in scenarios with low vaccine coverage (< 80%).…”
Section: Methodsmentioning
confidence: 99%
“…The impact data on its effect are available from Saudi Arabia, which introduced universal VV in 2008 with a two dose schedule, and a study using health insurance data found an overall 60% reduction in the proportion of disease in children aged between 1-4 years after introduction. 31,75 Herd immunity and shift to older age groups An indirect effect of VV in non-vaccinated age groups has been described in many studies. As herd immunity is more pronounced in age groups closer to the vaccinated group, there are concerns about a shift of the disease to older age groups, which have a higher rate of complications.It is more likely in scenarios with low vaccine coverage (< 80%).…”
Section: Methodsmentioning
confidence: 99%
“…Complications such as bacterial skin superinfections, pneumonia, bronchitis, laryngotracheitis, and gastrointestinal tract disorders are the most characteristic in children under two years of age. Cerebellar ataxia, encephalitis, aseptic meningitis, transverse myelitis, and Guillain-Barre syndrome are the main viral CNS complications, they are more frequent in children 3-6 years of age [8,9]. Peripheral facial palsy, described by Hanalioğlu et al [10], is an extremely rare neurologic complication of varicella.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of VZV differs across the world with a lower seroprevalence in adults found in tropical and subtropical climates and higher rates found in temperate climates, e.g. from 58% in Puerto Rico to 86%-99% in Mexico [43,45,46]. In Europe, the majority of children acquire VZV infection before adulthood in age groups <5 and 5-9 years with a variability seen in different countries [43].…”
Section: Vzv Seroprevalencementioning
confidence: 99%